Antinociceptive activity of doliroside B. (31st December 2023) - Bai, Xishan; Li, Yanhong; Li, Yuxiao; Li, Min; Luo, Ming; Tian, Kai; Jiang, Mengyuan; Xiong, Yong; Lu, Ya; Li, Yukui; Yu, Haibo; Huang, Xiangzhong
Abstract: Context: Dolichos trilobus Linn (Leguminosae) is often used in Yi ethnic medicine to treat pain, fracture, and rheumatism. Objective: To explore the therapeutic potential of doliroside B (DB) from D. trilobus and its disodium salt (DBDS) and the underlying mechanism in pain. Materials and methods: In the writhing test, Kunming mice were orally treated with DB and DBDS at doses of 0.31, 0.62, 1.25, 2.5, and 5 mg/kg. Vehicle, morphine, indomethacin, and acetylsalicylic acid were used as negative and positive control on the nociception-induced models, respectively. In the hot plate test, mice were orally treated with DB and DBDS at doses of 2.5, 5, 10, and 20 mg/kg. In the formalin test, mice were orally treated with DB and DBDS at doses of 2.5, 5, 10, and 20 mg/kg. In the meanwhile, lipopolysaccharide-induced inflammatory model in RAW264.7 macrophages was adopted to study the mechanism of pain alleviation for DBDS. Results: DBDS (5 mg/kg) inhibited the writhing number by 80.2%, which exhibited the highest antinociceptive activity in pain models. DBDS could selectively inhibite the activity of COX-1. Meanwhile, it also reduced the production of NO, iNOS, and IL-6 by 55.8%, 69.0%, and 49.9% inhibition, respectively. It was found that DBDS also positively modulated the function of GABAA1 receptor. Discussion and conclusions: DBDS displayed antinociceptive activity by acting on both the peripheral and central nervous systems, which may act on multitargets. Further work is warranted for developing DBDS into a potential drug for the treatment of pain.